Exhaustion From the Emotional Labour of Frontline Employees in the Hospitality Industry in China - Ma, Zheng (Auckland University of Technology, 2021)
Emotional labour is the effort employees put into expressing emotions required by the organisation and curtailing the expression of those emotions that are not. The work of frontline employees in the hospitality industry is typically reliant on emotional labour because they have direct contact with and interaction with customers; therefore, this process is more likely to lead to high levels of emotional expression. Current research shows that excessive emotional expression or repression can lead to emotional exhaustion, which is also a common problem faced by frontline hospitality employees. This study attempts to explore the consequences of exhaustion from the emotional labour experienced by frontline employees in the hospitality industry and propose solutions for the employers. The study will collect data from one-on-one interviews with five frontline employees from the hospitality industry in China.
Keywords: Emotional Labour; Emotional Exhaustion; Frontline Employee; Hospitality Industry